The impact of emotional and spiritual intelligence on students' personal financial management behavior, parenting style as a mediator - Janri D. Manafe; Tuti Setyorini (Institute of Computer Science (IOCS), 2023)
This study discusses financial management behavior and its relationship with emotional intelligence and spiritual intelligence in students at State Universities in Kupang City, East Nusa Tenggara. The lack of awareness of saving among the public and consumptive behavior in Indonesia are the background of this study. High emotional intelligence is expected to help in making wise financial decisions. Spiritual intelligence is also thought to play a role in shaping positive attitudes and behaviors in managing personal finances. This study aims to examine the influence of emotional and spiritual intelligence, as well as parenting as a mediator on student financial management behavior. Questionnaires are used in data collection. The analysis was carried out with a Structural Equation Modeling (SEM) approach. The results are expected to provide insight into the factors that influence financial management behavior in students, which can be the basis for a more effective financial education program